2013
DOI: 10.1007/s12013-013-9640-6
|View full text |Cite
|
Sign up to set email alerts
|

The −319C/+49G/CT60G Haplotype of CTLA-4 Gene Confers Susceptibility to Rheumatoid Arthritis in Mexican Population

Abstract: Several single nucleotide polymorphisms (SNPs) within the CTLA-4 gene and elevated serum levels of soluble CTLA-4 (sCTLA-4) have been associated with autoimmunity including rheumatoid arthritis (RA). In this case-control study, we evaluated the relationship between the -319C/T (rs5742909) and CT60 G/A (rs3087243) SNPs and sCTLA-4 levels in 200 RA patients and 200 control subjects (CS) from Western Mexico. Both SNPs were genotyped with the polymerase chain reaction-restriction fragment length polymorphism techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…The CT60 *G allele has been extensively studied, but its frequency changes with ethnicity. In our population, the minor allele frequency (MAF) of this variant in controls group (MAF ≤50%) was found similar to those reported in European (Farago et al., ) Tunisian (Benmansour et al., ) and Chinese Han (Wang et al., ) populations, whereas it was different (MAF >50%) in Asian (Lei et al., ; Tsukahara et al., ) and American populations (Pincerati et al., ; Torres‐Carrillo et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…The CT60 *G allele has been extensively studied, but its frequency changes with ethnicity. In our population, the minor allele frequency (MAF) of this variant in controls group (MAF ≤50%) was found similar to those reported in European (Farago et al., ) Tunisian (Benmansour et al., ) and Chinese Han (Wang et al., ) populations, whereas it was different (MAF >50%) in Asian (Lei et al., ; Tsukahara et al., ) and American populations (Pincerati et al., ; Torres‐Carrillo et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in accordance with several studies, which have shown associations between this variation and risk of COPD , Graves disease , autoimmune type 1 diabetes , acute anterior uveitis and multi‐factorial autoimmune diseases . However, this association was not found for Behcet disease , RA , and systemic lupus erythematosus . The TT genotype at −318 C/T has been shown to be associated with upregulation of CTLA4 transcription .…”
Section: Discussionsupporting
confidence: 91%
“…Four articles were excluded because 2 were review articles, 1 contained duplicate data, and 1 had no data concerning the polymorphisms. Thus, 19 studies met our inclusion criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They consisted of 8 studies on the CTLA-4 polymorphism with 2093 patients and 2480 controls, 5 on the CD226 polymorphism with 2278 patients and 1940 controls, 6 on the FAS polymorphism with 546 patients and 618 controls, and 3 on the FASL polymorphism with 321 patients and 307 controls (Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…While some studies have found that CTLA-4 rs5742909, CD226 rs763361, FAS-670 rs1800682, and FASL rs763110 polymorphisms are associated with RA, other studies have reported no such association [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. To overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false positive or false negative associations [32][33][34], we performed a meta-analysis to determine whether these polymorphisms are associated with RA susceptibility.…”
Section: Introductionmentioning
confidence: 97%